A study of campus romance among diploma students in UiTM Kampus Samarahan / Mohd Khairul Hakimin Muthar ... [et al.] - Muthar, Mohd Khairul Hakimin; Alias, Kamaliah; Surip, Nuraine; Yaacob, Rohana; Murad, Siti Nordayana (2005)
Different people have different perception about love. It depends on how we understand and experienced towards our feeling. It is deeply connected with our heart and mind, soul on how we create the love. We always heard about the legend of love like Romeo and Juliet, Leia and Majnun, and Uda and Dara, which allow us to evaluate the value of love in our society. Love comes from different aspects. It does not mean love only from a person to a person. Love also can come from a person to a God, to a nature, country and so on. Love to another than a person does not affect much to the feeling of human being. Different aspects of love create different consequences. It is because the level of our feeling of love is different. Love is different. Love to God is everlasting but love to human being can change. The changes sometimes lead to broken heart and even unreasonable action. That is why our research stress on the implication of love among student in order to see how the performance towards their studies when they are falling in love. It might be good or bad implication that depend on individual.